GOVERNANSI KORPORAT DAN PRAKTIK MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR TERBUKA DI INDONESIA - Ardhya Yudistira Adi Nanggala (Universitas Muhammadiyah Jember, 2019)
This study aims to determine and analyze the effect of corporate governance mechanisms on laboratory management. The governance mechanisms tested are institutional ownership, managerial ownership, the proportion of independent commissioners, the number of commissioners, and the audit committee. Population of this study is manufacturing companies listed on the Stock Exchange from 2015-2017. Sampling was done by purposive sampling method. Research data could be obtained from www.idx.co.id. Based on the results of the study concluded that the corporate governance mechanism consisting of managerial ownership, institutional ownership, the proportion of independent commissioners, the size of the board of commissioners, and the existence of an audit committee had no effect on earnings management